ABO and Rhesus (D) Blood Group Distribution among Nigerians in Ojo Area, Lagos State, Nigeria - Odegbemi, O.B., Atang, E.B., Atapu, D.A., Jonathan, J.P., Okunola, O.A., Festus, O., Odegbemi, A.O. (Sokoto Journal of Medical Laboratory Science)
ABO and Rhesus blood groups are known to vary from one population to another. They are the most clinically significant and prevalent blood group systems. Their relevance in blood transfusion science cannot be over emphasized. This study was designed for the purpose of updating information on the prevalence and distribution of ABO and Rh (D) blood groups among residents of Navy town, Ojo and its environs, Lagos State, Nigeria. ABO and Rhesus (D) phenotyping was carried out using standard tube techniques . Three thousand six hundred and four participants were recruited for this study. Gender distribution indicated that 2159 (59.9%) were females while 1445 (40.1%) were male. ABO blood group distribution indicated that 1868 (51.8%) were blood group O, 949 (26.3%) were blood group A, 657 (18.2%) group B and 130 (3.6%) were group AB. Of all the subjects tested, 3360 (93.3%) were Rh (D) positive while 244 (6.7%) were Rh (D) negative. The Rh D positive and Rh D negative distribution varied among the 4 ABO blood groups with O Rh D positive being the highest with 1786 (48.4%) while AB Rh D negative was the least with 6 (1.2%). The higher proportion of blood group O in this study is an advantage because blood group O blood that are negative for high titre anti A and B can potentially be transfused against ABO blood group barrier to group A, B and AB recipient. The low prevalence of Rh (D) negative blood group can also potentially reduce the incidence of Rhesus (D) -related haemolytic disease of the foetus and newborn in our environment particularly in the absence of universal access to prophylactic immunoglobulin D.